Electrocatalyst for removing nitrate nitrogen in water environment and producing ammonia directionally, preparation method and application thereof

CN122999259APending Publication Date: 2026-10-30SHANGHAI UNIV OF ENG SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611509654.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]现有电催化脱硝材料仍存在诸多短板:贵金属催化性能优异,但储量稀缺、成本高昂,难以工程化应用;单非贵金属催化剂活性位点单一,亚硝态氮中间体大量累积,氨选择性与法拉第效率偏低;LDH、MOFs、钙钛矿等新型催化材料制备工艺复杂,水相稳定性差,易粉化脱落,对低浓度废水(约500 mg/L硝酸根)处理效果有限,极大限制了实际应用

Benefits of technology

1. 首创“硫元素桥”耦合双金属合金的双功能氢调控机制,精准管控亚硝酸根中间体积累、降低水环境次生危害:现有常规Cu-Ni基电催化体系普遍仅依靠双金属简单“接力催化”机制实现脱硝产氨,即仅利用Cu位点吸附硝态氮并断裂N-O键生成亚硝酸根中间体、Ni位点辅助中间体加氢转化,催化机制单一,对反应过程中的活性氢调控能力薄弱。该类传统催化体系存在明显技术短板,低工作电位下析氢副反应(HER)竞争剧烈,活性氢利用效率低下,极易造成亚硝酸根中间体大量堆积,不仅大幅降低氨选择性与催化反应效率,更会引发严重的水环境安全问题。现有公开技术的研究重点大多聚焦于硝态氮的去除效率与产氨性能,忽视了脱硝过程中亚硝酸根中间体累积带来的二次污染风险,存在明显的技术短板与应用局限性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999259A_ABST
    Figure CN122999259A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of water treatment, and particularly relates to an electrocatalyst for removing nitrate nitrogen in a water environment and producing ammonia in a targeted manner, as well as a preparation method and application thereof. The electrocatalyst for removing nitrate nitrogen and producing ammonia in a targeted manner is prepared by grinding and uniformly mixing a sulfur-doped graphite phase carbon nitride precursor and a copper-nickel double-metal complex precursor, then performing ball-milling homogenization treatment, and then being calcined in an inert atmosphere. The electrocatalyst effectively solves the technical problems of high cost of traditional catalysts, accumulation of nitrite nitrogen intermediates, easy agglomeration of active sites, and poor stability, and has the advantages of simple preparation process, cheap and easily available raw materials, strong repeatability, excellent denitration efficiency and ammonia selectivity, and the like. The electrocatalyst can be coupled with a photovoltaic system to realize low-energy-consumption green operation, and simultaneously complete purification of nitrate-containing wastewater and resource recycling of green ammonia, and is suitable for agricultural and industrial nitrate-containing wastewater treatment, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment technology, specifically relating to a method for preparing a sulfur-doped copper-nickel alloy / carbon composite electrocatalyst. This catalyst can efficiently electrocatalyze the reduction of nitrate nitrogen in water and directionally produce ammonia, and is suitable for photovoltaic-coupled green ammonia preparation and agricultural and industrial nitrate-containing wastewater resource utilization systems. Background Technology

[0003] Traditional treatment of nitrate-containing wastewater mainly relies on biological denitrification, which suffers from drawbacks such as large sludge production, poor salt tolerance, and low efficiency at low temperatures. Industrial ammonia synthesis uses the Haber-Bosch process, which is energy-intensive, generates significant carbon emissions, and cannot achieve nitrogen recycling. Electrocatalytic nitrate reduction can directionally reduce nitrate nitrogen to ammonia at ambient temperature and pressure, simultaneously achieving pollutant removal and resource recovery. This represents a core technological direction for green water treatment and green ammonia production.

[0004] Existing electrocatalytic denitrification materials still have many shortcomings: precious metals have excellent catalytic performance, but their reserves are scarce and their costs are high, making them difficult to apply in engineering; single non-precious metal catalysts have a single active site, resulting in a large accumulation of nitrite intermediates and low ammonia selectivity and Faraday efficiency; novel catalytic materials such as LDH, MOFs, and perovskites have complex preparation processes, poor aqueous phase stability, and are prone to pulverization and detachment, and their treatment effect on low-concentration wastewater (about 500 mg / L nitrate) is limited, which greatly restricts their practical application.

[0005] Copper and nickel bimetals exhibit excellent synergistic catalytic effects, but they still suffer from defects such as easy aggregation of active sites, insufficient precision in doping control, insufficient electronic structure control, severe hydrogen evolution side reactions, and poor catalytic stability. These defects lead to poor matching of catalyst material parameters and insufficient performance reproducibility. In addition, the lack of standardized electrode preparation processes and the construction of precise and stable three-electrode testing systems result in low accuracy of testing systems and non-standard processes, making it difficult to support catalyst performance evaluation and engineering scale-up. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention uses a sulfur-doped, pleated, stacked porous carbon sheet substrate as a conductive carrier, a copper-nickel bimetallic core as the catalytic active center, and in-situ thiourea doping to construct a "sulfur bridge" to precisely control the hydrogenation reaction pathway. A highly active and stable sulfur-doped copper-nickel alloy / carbon composite electrocatalyst powder is prepared through a multi-step process involving precursor preparation, metal complexation, ball milling homogenization, and high-temperature calcination. Simultaneously, a standardized electrode drop-coating process and a three-electrode testing system are implemented, efficiently removing nitrate nitrogen from water while precisely controlling the accumulation of nitrite nitrogen to achieve targeted ammonia production, demonstrating excellent prospects for large-scale application.

[0007] The technical solution of the present invention is a method for preparing an electrocatalyst for removing nitrate nitrogen from an aqueous environment and directionally producing ammonia. The steps include: grinding and mixing a sulfur-doped graphitic carbon nitride precursor and a copper-nickel bimetallic complex precursor, then performing ball milling homogenization treatment, and finally calcining in an inert atmosphere to obtain the electrocatalyst.

[0008] The mass ratio of the sulfur-doped graphitic carbon nitride precursor to the copper-nickel bimetallic complex precursor is 1.5-2.5:1, preferably 1.9-2.1:1, and in one embodiment, it is 2:1.

[0009] The ball milling homogenization process includes the following repeated steps: forward rotation, dwell, reverse rotation, and dwell. The ball mill speed is 300-500 r / min, preferably 350 r / min; the forward rotation time is 10-20 min, preferably 15 min; the reverse rotation time is 10-20 min, preferably 15 min; and the dwell time is 10-20 min, preferably 15 min. The ball milling duration is 90-100 min. The ball mill is a planetary ball mill.

[0010] The inert atmosphere is argon.

[0011] The calcination temperature is 800-900℃, preferably 800℃; the calcination time is 4-5h, preferably 4h. The temperature is increased to the calcination temperature at a heating rate of 5-6℃ / min.

[0012] The preparation of the sulfur-doped graphitic carbon nitride precursor includes: grinding and mixing melamine, maleic hydrazine, and thiourea, followed by calcination under an inert atmosphere.

[0013] The mass ratio of melamine, maleic hydrazine, and thiourea is 10-45:0.1-1.5:1, preferably 20-45:0.4-1:1, more preferably 38-43:0.5-0.7:1, even more preferably 39-41:0.5-0.6:1, and in one embodiment, it is 40:0.5:1.

[0014] The inert atmosphere is nitrogen.

[0015] The calcination temperature is 500-600℃, preferably 550℃; the calcination time is 4-5h, preferably 4h. The temperature is increased to the calcination temperature at a heating rate of 5-6℃ / min.

[0016] The preparation of the copper-nickel bimetallic complex precursor includes: mixing and reacting copper salt, nickel salt, and melamine in an aqueous alcohol solution. Specifically, the aqueous solution containing copper salt and nickel salt is mixed and reacted with an anhydrous alcohol solution containing melamine.

[0017] The alcohol-water solution is a mixture of anhydrous ethanol and water, with a volume ratio of anhydrous ethanol to water of 4.5-5.5:1, preferably 4.9-5.1:1, and in one embodiment, 5:1.

[0018] In the alcohol-water solution, the total concentration of metal ions is 0.05-0.2 mol / L, preferably 0.05-0.1 mol / L, more preferably 0.075-0.085 mol / L, and in one embodiment, 0.083-0.084 mol / L; the molar ratio of copper ions in the copper salt to nickel ions in the nickel salt is 1:0.3-8, preferably 1:0.3-0.5 or 1:2-8, more preferably 1:3-4, and in one embodiment, 1:3; the concentration of melamine is 0.01-0.1 g / mL, preferably 0.01-0.05 g / mL, and in one embodiment, 0.03-0.04 g / mL. The copper salt is selected from at least one of copper sulfate pentahydrate, copper nitrate trihydrate, copper chloride dihydrate, and copper bromide, preferably copper chloride dihydrate. The nickel salt is selected from at least one of nickel sulfate hexahydrate, nickel chloride hexahydrate, nickel nitrate hexahydrate, nickel sulfate heptahydrate, and nickel acetate tetrahydrate, preferably nickel chloride hexahydrate.

[0019] The reaction is carried out at room temperature with stirring, and the reaction time is 12-14 hours.

[0020] After the reaction was completed, the supernatant was removed by centrifugation at 8000 rpm, anhydrous ethanol was added, and the mixture was centrifuged again at 8000 rpm. This process was repeated three times. The resulting solid was then vacuum dried at a temperature of 80±5℃.

[0021] This invention provides an electrocatalyst for removing nitrate nitrogen and directionally producing ammonia. It is prepared using the method described above for preparing the electrocatalyst for removing nitrate nitrogen and directionally producing ammonia in aquatic environments. A Cu-Ni alloy catalyzes the cracking of graphitic carbon nitride (g-C3N4) to generate a wrinkled, stacked porous carbon sheet matrix. Sulfur atoms are embedded in the carbon lattice of the porous carbon sheet matrix. Cu-Ni alloy nanoparticles are uniformly embedded and anchored on the surface of the porous carbon sheet matrix. The porous carbon sheet matrix is ​​stacked and overlapped to construct a continuous, interconnected three-dimensional porous layered network. Abundant mesopores and macropores are formed between the porous carbon sheet matrix, significantly increasing the specific surface area. The copper in the electrocatalyst of this invention can efficiently adsorb nitrate nitrogen and break NO bonds to generate NO2. -Nickel enhances the hydrogenation conversion of intermediates and effectively inhibits nitrite accumulation; sulfur doping can precisely control the electronic structure of carbon-based supports, optimize the adsorption energy of active sites, suppress hydrogen evolution side reactions, and significantly improve catalytic selectivity. This invention, based on the hydrogen regulation effect of the synergistic effect of sulfur-bridged bimetallic alloys and a three-dimensional continuous porous layered network, achieves a low operating potential of -0.5 to -0.8 V (vs. RHE) (especially -0.6 to -0.8 V (vs. RHE) at room temperature and pressure, in a neutral aquatic environment, and with low NO3 concentrations. - This highly efficient catalytic hydrogenation method for targeted NH3 production significantly suppresses the intensely competitive hydrogen evolution side reaction at low operating potentials, avoids secondary pollution caused by nitrite nitrogen accumulation, and is directly suitable for the treatment needs of low-concentration nitrate-containing wastewater in municipal, agricultural, and industrial applications, promoting the production of NO3-containing wastewater. - Resource utilization and high-value utilization of wastewater.

[0022] The electrocatalyst provided by this invention for removing nitrate nitrogen and directionally producing ammonia can be used to prepare working electrodes and electrolysis devices for the ammonia conversion and removal of nitrate nitrogen and the preparation of liquid nitrogen fertilizer.

[0023] The present invention provides a working electrode for removing nitrate nitrogen and producing directional ammonia, comprising a matrix and an electrocatalyst for removing nitrate nitrogen and producing directional ammonia coated on the matrix. The matrix is ​​carbon paper.

[0024] The electrolytic device for removing nitrate nitrogen and directionally producing ammonia provided by the present invention includes a working electrode for removing nitrate nitrogen and directionally producing ammonia, as provided by the present invention. Further, it also includes a counter electrode and a reference electrode, wherein the counter electrode is a platinum electrode and the reference electrode is a saturated potassium chloride-silver chloride electrode.

[0025] The present invention provides a method for removing nitrate nitrogen and directionally producing ammonia, comprising the following steps: placing the working electrode, counter electrode and reference electrode provided by the present invention for removing nitrate nitrogen and directionally producing ammonia in a sample solution, and performing electrolysis at room temperature and pressure to reduce nitrate nitrogen in the sample solution to ammonium ions, or treating the sample solution at room temperature and pressure using the electrolysis device provided by the present invention for removing nitrate nitrogen and directionally producing ammonia to reduce nitrate nitrogen in the sample solution to ammonium ions.

[0026] Furthermore, the working electrode for removing nitrate nitrogen and directional ammonia production provided by the present invention serves as a cathode unit with a voltage of -0.5 to -0.8V, preferably -0.6 to -0.8V, and more preferably -0.6 to -0.7V.

[0027] Furthermore, the sample liquid includes, but is not limited to, industrial wastewater, agricultural wastewater, and domestic wastewater.

[0028] This invention provides a liquid nitrogen fertilizer, which is prepared by the method described above for removing nitrate nitrogen and producing ammonia in a targeted manner.

[0029] The beneficial effects of this invention are as follows: 1. A pioneering bifunctional hydrogen regulation mechanism using a "sulfur bridge" coupled with a bimetallic alloy precisely controls the accumulation of nitrite intermediates and reduces secondary hazards to the aquatic environment: Existing conventional Cu-Ni-based electrocatalytic systems generally rely solely on a simple bimetallic "relay catalysis" mechanism to achieve denitrification and ammonia production. This involves using Cu sites to adsorb nitrate nitrogen and break NO bonds to generate nitrite intermediates, followed by Ni sites assisting in the hydrogenation conversion of these intermediates. This catalytic mechanism is singular and lacks control over active hydrogen during the reaction. Such traditional catalytic systems have significant technical shortcomings. At low operating potentials, competition from the hydrogen evolution reaction (HER) is intense, resulting in low active hydrogen utilization efficiency and a high risk of nitrite intermediate accumulation. This not only significantly reduces ammonia selectivity and catalytic reaction efficiency but also poses serious aquatic safety risks. Current research on publicly available technologies largely focuses on nitrate nitrogen removal efficiency and ammonia production performance, neglecting the secondary pollution risks caused by nitrite intermediate accumulation during denitrification, resulting in significant technical limitations and application constraints.

[0030] This invention breaks through the technical bottleneck of traditional bimetallic catalysis and proposes for the first time a bifunctional hydrogen regulation effect coupled with a sulfur element bridge in a bimetallic alloy. By relying on the covalent doping of sulfur atoms into a porous carbon skeleton, a dedicated hydrogenation regulation channel is constructed, achieving precise control and efficient conversion of nitrite intermediates across the entire potential range: at low overpotentials, sulfur active sites can directionally guide the precise delivery of active hydrogen to the surface of the nitrite intermediate, enhancing the hydrogenation reduction reaction of the intermediate and suppressing competition from hydrogen evolution side reactions at the source, significantly reducing the generation and accumulation of nitrite; at high overpotentials, the sulfur element bridge can open a hydrogenation "side gate channel," effectively diverting the hydrogen flux of the main nitrite hydrogenation reduction reaction, alleviating the pressure of the hydrogenation reaction, reducing hydrogen evolution competition in the main reaction channel, ensuring continuous and efficient conversion of nitrite intermediates, and avoiding intermediate retention and enrichment.

[0031] This original regulatory mechanism can significantly reduce the peak concentration of nitrite nitrogen in the system from 12.53 mg / L in the sulfur-free system to 6.5 mg / L, achieving efficient decomposition and control of toxic intermediates across the entire operating potential range. Compared to a single copper catalytic system, the copper-nickel alloy composite catalyst of this invention reduces nitrite nitrogen accumulation by more than 60%, completely solving the industry pain point of large accumulation of nitrite intermediates in traditional denitration catalysis. Under optimal sulfur doping process and operating potential of -0.7 V, this catalyst achieves an ammonia selectivity of 95% and an ammonia yield of 342.08 μg·h⁻¹. -1 ·cm -2 It combines excellent catalytic efficiency with ammonia production selectivity.

[0032] Compared to existing publicly available technologies that only focus on nitrate nitrogen removal and green ammonia resource utilization, this invention also focuses on the environmental safety of the catalytic reaction process. Through a unique sulfur-bridged hydrogen regulation mechanism, it curbs the accumulation of toxic nitrite intermediates from the source of the reaction, effectively avoiding secondary environmental problems such as water toxicity pollution and ecological damage caused by nitrite residues. While achieving efficient purification and resource utilization of nitrate-containing wastewater, it greatly reduces the environmental risks of the water treatment process. This is the core original advantage of this invention, which distinguishes it from similar denitrification and ammonia production catalysts, and it has higher practical water environment engineering application value and ecological safety value.

[0033] 2. Currently reported MOF-based and bimetallic electrocatalytic ammonia production technologies largely rely on stringent experimental conditions of high nitrate nitrogen substrate concentrations and industrial-grade high current densities. Their advantages are primarily evident in high-pollution, high-concentration wastewater resource recovery scenarios. However, when switching to low-concentration nitrate nitrogen environments, they are often constrained by problems such as intensified hydrogen evolution side reactions and limited substrate mass transfer, leading to a significant decline in ammonia selectivity and conversion efficiency. This makes them unsuitable for mainstream real-world water conditions such as agricultural non-point source wastewater, municipal sewage, and general industrial low-concentration nitrate wastewater, severely limiting their engineering applications. Most published literature also focuses on optimizing catalytic indicators under high-concentration nitrate nitrogen systems, paying insufficient attention to the widespread low-concentration nitrate nitrogen pollution control scenarios in real-world environments, resulting in significant shortcomings in the adaptability of these technologies to various operating conditions. The composite electrocatalyst prepared in this invention was used to verify its performance under typical low-concentration nitrate pollution conditions (500 mg / L) in water bodies. It requires no industrial-grade high current and can operate stably under mild conditions in a neutral water environment with a potential range of -0.5 to -0.8 V (vs. RHE). The overall reaction conditions are mild, effectively reducing energy consumption. At a potential of -0.7 V, it can achieve a nitrate nitrogen conversion rate of 80%, ammonia selectivity of 95%, a Faraday efficiency of 59%, and an ammonia yield of 342.08 μg·h⁻¹. -1 ·cm -2 During the reaction, the peak concentration of nitrite nitrogen was only 6.5 mg / L, and the accumulation level of byproducts was controllable. At a potential of -0.6 V, the system achieved a Faradaic efficiency of 67%, a nitrite nitrogen conversion rate of 84%, an ammonia selectivity of 89%, and an ammonia yield of 336.87 μg·h⁻¹. -1 ·cm -2 Compared with existing studies on electrocatalytic ammonia conversion with low nitrate nitrogen (which typically have conversion rates of around 50% and Faradaic efficiencies of around 40%, and most lack monitoring data on nitrite nitrogen accumulation), this catalyst, under mild operating conditions with low substrate concentration and low overpotential, balances nitrate nitrogen conversion capacity, ammonia product selectivity, Faradaic efficiency, and low nitrite nitrogen accumulation, demonstrating outstanding comprehensive catalytic performance advantages.

[0034] 3. Stable support structure and high utilization rate of active sites: Compared with existing novel catalytic materials such as MOF, LDH, and perovskite, which generally suffer from poor aqueous phase stability, easy pulverization and detachment, framework collapse under complex water conditions, rapid performance degradation over long-term operation, and difficulty in adapting to the complex components of real wastewater, the catalyst of this invention uses a pleated stacked porous carbon sheet matrix conductive support to form an interwoven three-dimensional porous continuous network with a large specific surface area and excellent conductivity. 1) The carbon matrix has stable chemical properties and strong resistance to salt and impurity impact loads; 2) Uniformly dispersed copper-nickel bimetallic active sites, copper-nickel alloy nanoparticles are uniformly anchored on the surface of the folded and stacked porous carbon sheet matrix. High-temperature calcination results in a strong bond, making it less prone to agglomeration and detachment. It can withstand long-term continuous water treatment conditions, and its cycle stability and service life are greatly improved, which is significantly better than crystalline porous materials.

[0035] 4. Hierarchical porous structure adapted to water treatment mass transfer and strong anti-clogging ability: Existing materials such as diatomic MOFs are mainly microporous, resulting in high diffusion resistance between substrates and products. In actual wastewater systems, the pores are easily clogged by suspended solids and impurities, leading to rapid performance degradation. The pleated stacked porous carbon sheet matrix of the catalyst in this invention has a mesoporous-macroporous hierarchical structure with a high specific surface area, allowing for rapid diffusion and mass transfer of electrolyte, nitrate nitrogen substrate, and reaction intermediates. This ensures sufficient exposure of catalytic sites, reduces the risk of clogging in actual wastewater, and is more suitable for the fluid conditions of real water treatment.

[0036] 5. Controllable process parameters and good reproducibility: Through four sets of single-factor experiments on metal ratio, total metal loading, sulfur doping amount, and working potential, the optimal preparation and application parameters were determined. The catalytic performance showed a regular and stable volcano-shaped change curve, the process had strong repeatability, and it could be prepared in batches.

[0037] 6. The testing system is precise and standardized, suitable for scientific research and engineering applications: It adopts a standard three-electrode system of platinum sheet counter electrode + silver chloride reference electrode, combined with a standardized catalyst drop-coating electrode preparation process. The test data has high accuracy and good stability, which is suitable for laboratory performance evaluation and can also provide reliable parameter support for industrial equipment scale-up.

[0038] 7. Inexpensive and readily available raw materials, low preparation cost: Compared with existing conductive MOFs and single-atom catalysts that rely on expensive organic ligands and precise site control for synthesis, resulting in complex preparation processes, high raw material costs, and difficulties in large-scale production, and precious metal catalysts that are limited by resource reserves and have extremely high engineering application costs, this invention uses non-precious metals such as copper and nickel, along with inexpensive thiourea and melamine as core raw materials. It can be prepared simply by ball milling homogenization and high-temperature calcination in a tube furnace. The preparation equipment only requires a ball mill and a tube furnace, eliminating the need for complex processes such as high pressure, electrodeposition, and precise coordination synthesis. The entire set of process parameters is controllable and highly reproducible, allowing for stable mass production in a single batch. The preparation process is simple and has a low threshold for industrialization. Attached Figure Description

[0039] Figure 1 This diagram shows the water contact angle of Cu-Ni / NC electrocatalysts with different Cu / Ni molar ratios. It is used to characterize the variation of the hydrophilicity / hydrophobicity properties of the catalyst surface under different metal ratios.

[0040] Figure 2 Line graphs showing the variation of water contact angle for Cu-Ni / NC electrocatalysts with different Cu / Ni molar ratios are used to characterize the changes in the hydrophilicity and hydrophobicity of the catalyst surface under different metal ratios.

[0041] Figure 3 This is a high-resolution XPS fine spectrum (Cu 2p) of the Cu1Ni3 / NC electrocatalyst. It is used to demonstrate the successful preparation of the Cu-Ni alloy, its elemental valence states, and crystal structure characteristics.

[0042] Figure 4 This is a high-resolution XPS fine spectrum (Ni 2p) of the Cu1Ni3 / NC electrocatalyst. It was used to demonstrate the successful preparation of the Cu-Ni alloy, its elemental valence states, and crystal structure characteristics.

[0043] Figure 5 This is the XRD phase diffraction pattern of the Cu1Ni3 / NC electrocatalyst. It is used to demonstrate the successful preparation of the Cu-Ni alloy, its elemental valence states, and crystal structure characteristics.

[0044] Figure 6 SEM images of Cu-Ni / NC electrocatalysts prepared with different Cu / Ni molar ratios (Cu1Ni0, Cu3Ni1, Cu2Ni1, Cu1Ni1) were obtained. The differences in surface micromorphology, pore structure, and active site distribution of the materials under different metal ratios were compared and analyzed.

[0045] Figure 7SEM images of Cu-Ni / NC electrocatalysts prepared with different Cu / Ni molar ratios (Cu1Ni2, Cu1Ni3, Cu1Ni4, Cu1Ni8) were obtained. The differences in surface micromorphology, pore structure, and active site distribution of the materials under different metal ratios were compared and analyzed.

[0046] Figure 8 The graph shows the current density versus voltage for Cu-Ni / NC electrocatalysts with different Cu / Ni molar ratios. The dashed line in the graph represents the absence of NO3. - Solid lines indicate the presence of NO3. - .

[0047] Figure 9 The Faradaic efficiency, selectivity, and conversion of Cu-Ni / NC electrocatalysts with different Cu / Ni molar ratios were evaluated at a nitrate concentration of 500 mg / L and a potential of -0.8 V (vs. RHE). Except for carbon paper, all catalysts with different ratios exhibited catalytic activity, with the copper-Ni-3 ratio showing a Faradaic efficiency exceeding that of the copper-Ni-4 ratio by more than 5 percentage points.

[0048] Figure 10 The curves show the change of nitrite concentration over time for Cu-Ni / NC electrocatalysts with different Cu / Ni molar ratios at a nitrate concentration of 500 mg / L and a potential of -0.8 V (vs. RHE).

[0049] Figure 11 The yield of NH3 in Cu-Ni / NC electrocatalysts with different Cu / Ni molar ratios is given at a nitrate concentration of 500 mg / L and a potential of -0.8 V (vs. RHE).

[0050] Figure 12 The graph shows the water contact angle of Cu1Ni3 / NC electrocatalysts with different total metal loadings. M15 represents a total metal loading of 15 mmol, M25 represents 25 mmol, and M35 represents 35 mmol. The lowest contact angle, 102.9°, is observed when the total metal loading is 25 mmol.

[0051] Figure 13 SEM images of Cu1Ni3 / NC electrocatalysts with different total metal loadings.

[0052] Figure 14 The curves show the current density versus voltage for Cu1Ni3 / NC electrocatalysts with different total metal loadings. The dashed line represents the absence of NO3. - Solid lines indicate the presence of NO3. - .

[0053] Figure 15The Faradaic efficiency, selectivity, and conversion of Cu1Ni3 / NC electrocatalysts with different total metal loadings at a nitrate concentration of 500 mg / L and a potential of -0.8 V (vs. RHE) were studied.

[0054] Figure 16 The curves show the change in nitrite concentration over time for Cu1Ni3 / NC electrocatalysts with different total metal loadings at a nitrate concentration of 500 mg / L and a potential of -0.8 V (vs. RHE).

[0055] Figure 17 The yield of NH3 in Cu1Ni3 / NC electrocatalysts with different total metal loadings is given at a nitrate concentration of 500 mg / L and a potential of -0.8 V (vs. RHE).

[0056] Figure 18 The Faraday efficiency, selectivity, and conversion of Cu1Ni3 / NC electrocatalyst with a total metal loading of 25 mmol at a nitrate concentration of 500 mg / L were determined at different potentials.

[0057] Figure 19 The curves show the change of nitrite nitrogen concentration over time at different potentials for Cu1Ni3 / NC electrocatalyst with a total metal loading of 25 mmol and a nitrate concentration of 500 mg / L.

[0058] Figure 20 The NH3 yield of Cu1Ni3 / NC electrocatalyst with a total metal loading of 25 mmol at a nitrate concentration of 500 mg / L was measured at different potentials. The catalytic performance at a total metal loading of 25 mmol exhibited a classic volcanic pattern, with the optimal potential being -0.7 V (vs. RHE).

[0059] Figure 21 XPS fine spectrum (Cu 2p) of the 0.1S-Cu1Ni3 / NC electrocatalyst prepared in Example 1.

[0060] Figure 22 The fine XPS spectrum (Ni 2p) of the 0.1S-Cu1Ni3 / NC electrocatalyst prepared in Example 1.

[0061] Figure 23 The fine XPS spectrum (S 2p) of the 0.1S-Cu1Ni3 / NC electrocatalyst prepared in Example 1.

[0062] Figure 24 XRD phase diffraction patterns of Cu1Ni3 / NC catalyst and 0.1S-Cu1Ni3 / NC electrocatalyst prepared in Example 1.

[0063] Figure 25The figures show the water contact angle measurements of S-Cu1Ni3 / NC electrocatalysts with different sulfur doping concentrations. Here, 0.05S-Cu1Ni3 represents a sulfur doping concentration of 0.05 g, 0.1S-Cu1Ni3 represents a sulfur doping concentration of 0.1 g, 0.2S-Cu1Ni3 represents a sulfur doping concentration of 0.2 g, and 0.4S-Cu1Ni3 represents a sulfur doping concentration of 0.4 g.

[0064] Figure 26 SEM images of S-Cu1Ni3 / NC electrocatalysts with different sulfur doping amounts.

[0065] Figure 27 The curves show the current density versus voltage for S-Cu1Ni3 / NC electrocatalysts with different sulfur doping levels.

[0066] Figure 28 The Faradaic efficiency, selectivity, and conversion of S-Cu1Ni3 / NC electrocatalysts with different sulfur doping concentrations were evaluated at a nitrate concentration of 500 mg / L and a potential of -0.7 V (vs. RHE). The selectivity, Faradaic efficiency, and conversion of 0.05S-Cu1Ni3 (0.05 g sulfur doping) and 0.1S-Cu1Ni3 (0.1 g sulfur doping) were not significantly different.

[0067] Figure 29 The curves show the nitrite concentration versus time for S-Cu1Ni3 / NC electrocatalysts with different sulfur doping amounts at a nitrate concentration of 500 mg / L and a potential of -0.7 V (vs. RHE). The nitrite concentration produced by 0.1S-Cu1Ni3 (0.1 g sulfur doping) is lower than that produced by 0.05S-Cu1Ni3 (0.05 g sulfur doping).

[0068] Figure 30 The yield of NH3 in S-Cu1Ni3 / NC electrocatalysts with different sulfur doping concentrations is given at a nitrate concentration of 500 mg / L and a potential of -0.7 V (vs. RHE).

[0069] Figure 31 The curves show the changes in nitrite concentration over time for Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst at a nitrate concentration of 500 mg / L and a potential of -0.5 V (vs. RHE).

[0070] Figure 32 The Faraday efficiency, selectivity, conversion and NH3 yield of Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst at a nitrate concentration of 500 mg / L and a potential of -0.5 V (vs. RHE) were investigated.

[0071] Figure 33The curves show the changes in nitrite concentration over time for Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst at a nitrate concentration of 500 mg / L and a potential of -0.6 V (vs. RHE).

[0072] Figure 34 The Faraday efficiency, selectivity, conversion and NH3 yield of Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst at a nitrate concentration of 500 mg / L and a potential of -0.6 V (vs. RHE) were investigated.

[0073] Figure 35 The curves show the changes in nitrite concentration over time for Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst at a nitrate concentration of 500 mg / L and a potential of -0.7 V (vs. RHE).

[0074] Figure 36 The Faradaic efficiency, selectivity, conversion and NH3 yield of Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst at a nitrate concentration of 500 mg / L and a potential of -0.7 V (vs. RHE) were investigated.

[0075] Figure 37 The curves show the changes in nitrite concentration over time for Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst at a nitrate concentration of 500 mg / L and a potential of -0.8 V (vs. RHE).

[0076] Figure 38 The Faraday efficiency, selectivity, conversion and NH3 yield of Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst at a nitrate concentration of 500 mg / L and a potential of -0.8 V (vs. RHE) were investigated.

[0077] Figure 39 Roughness profiles (a) for Cu-Ni / NC electrocatalysts with different Cu / Ni molar ratios, (b) for Cu1Ni3 / NC electrocatalysts with different total metal loadings, and (c) for S-Cu1Ni3 / NC electrocatalysts with different sulfur doping amounts.

[0078] Figure 40 Confocal laser scanning microscope images of Cu2Ni1 / NC electrocatalyst (a), Cu1Ni3 / NC electrocatalyst (b), and 0.1S-Cu1Ni3 / NC electrocatalyst (c).

[0079] Figure 41This is a schematic diagram of the overall working principle of the three-electrode electrocatalytic denitrification and ammonia production coupled with photovoltaic power supply system of the present invention, showing the three-electrode system structure consisting of platinum sheet counter electrode, catalyst working cathode and silver chloride reference electrode, and the electrocatalytic reaction process. Detailed Implementation

[0080] The present invention will now be described in detail with reference to specific embodiments. All reagents, raw materials, and instruments used in this invention are commercially available. Information on the main reagents, raw materials, and instruments used in this invention is as follows: Melamine (Shanghai Maclean Biochemical Technology Co., Ltd., Product No. M813390-500 g, 99%), Maleic hydrazine (Shanghai Yuanye Biotechnology Co., Ltd., Product No. S18042-100 g, 99%), Thiourea (Damas-beta, Product No. 71689C), Anhydrous sodium nitrate (Sinopharm Chemical Reagent Co., Ltd., Product No. 10019918, AR analytical grade), Anhydrous sodium sulfate (Sinopharm Chemical Reagent Co., Ltd., Product No. 10020518, AR analytical grade), Potassium chloride (Sinopharm Chemical Reagent Co., Ltd., Product No. 10016318, AR analytical grade), Silver chloride (Sinopharm Chemical Reagent Co., Ltd., Product No. 20036214, AR analytical grade), Copper chloride dihydrate (Sinopharm Chemical Reagent Co., Ltd., Product No. 10007818, AR... Analytical grade), nickel chloride hexahydrate (Sinopharm Chemical Reagent Co., Ltd., product number 10014218, AR analytical grade), anhydrous ethanol (Shanghai Titan Technology Co., Ltd., product number G73537IB, ≥99.9%), Nafion dispersion (Chemours, product number D520CS, Nafion D520). Dispersion, alcohol-based system, equivalent 1000, mass fraction 5%), conductive carbon paper (Shanghai Jingchong Electronic Technology Development Co., Ltd., HCP030N), planetary ball mill (Changsha Miqi Instrument Equipment Co., Ltd., YXQM-2L), tube furnace (Hefei Kejing Material Technology Co., Ltd., OTF-1200X), centrifuge (Hunan Xiangyi Laboratory Instrument Development Co., Ltd., H1850), vacuum drying oven (Shanghai Huitai Instrument Manufacturing Co., Ltd., DZF-6050), electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd., CHI650E), magnetic stirrer (Shanghai Sile Instrument Co., Ltd., 84-1A6S), CNC ultrasonic cleaner (Kunshan Ultrasonic Instrument Co., Ltd., KQ-800DB), intelligent constant temperature heating stage (Shenzhen Bangyuan Hardware Co., Ltd., BY105S), infrared heating lamp (PHILIPS, IR 250 RH IR2).

[0081] Example 1: Preparation of sulfur-doped Cu1Ni3 electrocatalyst and working electrode Catalyst preparation S1, Preparation of sulfur-doped g-C3N4 precursor: Weigh 4 g of melamine, 50 mg of maleic hydrazine and 0.1 g of thiourea, grind and mix thoroughly, transfer to an alumina crucible, heat to 550 ℃ at 5 ℃ / min under nitrogen atmosphere, calcine at constant temperature for 4 h, cool and grind into powder, the product is about 2 g.

[0082] S2, Preparation of bimetallic complex precursor: 25 mmol of total metal, including 6.25 mmol of copper chloride dihydrate and 18.75 mmol of nickel chloride hexahydrate (molar ratio 1:3), was dissolved in 50 mL of deionized water; 10 g of melamine was dispersed in 250 mL of anhydrous ethanol, mixed with the metal salt solution, and magnetically stirred at room temperature for 12 h; after centrifugation at 8000 rpm to remove the supernatant, anhydrous ethanol was added, and centrifugation was repeated at 8000 rpm three times. The resulting solid was dried under vacuum at 80 ℃ to obtain the metal complex precursor powder; S3, Composite Mixing Ball Milling: Weigh 2 g of sulfur-doped g-C3N4 powder and 1 g of metal complex precursor powder, grind and mix thoroughly, and then transfer to a planetary ball mill; run alternately at 350 r / min, for 15 min of forward rotation, 15 min of dwell, and 15 min of reverse rotation, for a total ball milling time of 90 min. S4, High-temperature calcination: The ball-milled powder was placed in a tube furnace under the protection of high-purity argon gas throughout the process, heated to 800℃ at 5℃ / min, calcined at a constant temperature for 4 h, and then naturally cooled to obtain sulfur-doped Cu1Ni3 electrocatalyst powder.

[0083] Working electrode preparation Weigh 2 mg of the above electrocatalyst powder and disperse it in 1 mL of anhydrous ethanol. Sonicate at 100 kW for 30 min. Add 20 μL of Nafion dispersion and sonicate again at 100 kW for 30 min to prepare a uniform slurry. Place 1×1 cm conductive carbon paper on a 50 ℃ heating table under infrared lamp conditions of 4. Apply the slurry by pipetting 0.5 mL onto each side of the conductive carbon paper. Dry the paper to obtain the working cathode.

[0084] Performance testing conditions: A three-electrode system of an electrochemical workstation was used, with a platinum sheet as the counter electrode and saturated potassium chloride and silver chloride as the reference electrode; 500 mg / L nitrate ions (prepared with anhydrous sodium nitrate), 0.1 mol / L Na2SO4 electrolyte, cathode working potential -0.7 V (vs. RHE), electrolysis at room temperature for 12 h.

[0085] Comparative Example 1: Different ratios of sulfur-free copper-nickel electrocatalysts (Cu3Ni1, Cu2Ni1, Cu1Ni1, Cu1Ni2, Cu1Ni3, Cu1Ni4, Cu1Ni8, Cu1Ni0) The catalyst preparation operation is the same as in Example 1, except that in S1, only g-C3N4 precursor is prepared without the addition of thiourea, and in the preparation of bimetallic complex precursor in S2, the molar ratio of copper chloride dihydrate to nickel chloride hexahydrate is set to 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:8, and 1:0, respectively.

[0086] The working electrode was prepared in the same manner as in Example 1.

[0087] The performance testing conditions are the same as in Example 1, except that the cathode working potential is -0.8 V (vs. RHE).

[0088] Comparative Example 2: Catalysts with different metal loadings (M15, M25, M35) The catalyst preparation procedure was the same as in Example 1, except that in S1, only the g-C3N4 precursor was prepared without the addition of thiourea, and in S2, the total amount of metal salts in the preparation of the bimetallic complex precursor was adjusted to 15 mmol, 25 mmol, and 35 mmol, respectively.

[0089] The working electrode was prepared in the same manner as in Example 1.

[0090] The performance testing conditions were the same as in Example 1, except that the cathode working potential was examined at -0.5 V, -0.6 V, -0.7 V, and -0.8 V (vs. RHE).

[0091] Comparative Example 3: Different sulfur-doped catalysts (0 g, 0.05 g, 0.1 g, 0.2 g, and 0.4 g of thiourea were added as sulfur sources, respectively). The catalyst preparation operation was the same as in Example 1, except that the amount of thiourea added in the preparation of the S1 sulfur-doped g-C3N4 precursor was 0 g, 0.05 g, 0.1 g, 0.2 g, and 0.4 g, respectively.

[0092] The working electrode was prepared in the same manner as in Example 1.

[0093] The performance testing conditions were the same as in Example 1, except that the cathode working potential was examined at -0.5 V, -0.6 V, -0.7 V, and -0.8 V (vs. RHE).

[0094] The microstructure of the samples was characterized by scanning electron microscopy (SEM), the material structure was analyzed by X-ray diffraction (XRD), the elemental composition and chemical state were analyzed by X-ray photoelectron spectroscopy (XPS), the hydrophilicity and hydrophobicity were measured by static contact angle measurement (sitting drop method), and the roughness was measured by confocal laser scanning microscope (CLSM).

[0095] I. Microscopic Morphology Analysis 1. Effect of copper-nickel molar ratio on morphology control SEM microstructure of undoped Cu-Ni / NC electrocatalyst as follows Figure 6 and Figure 7 As shown, 1) Cu1Ni0 (pure copper, Figure 6 a): Mainly composed of densely stacked amorphous carbon sheets, with dense agglomeration of the carbon matrix and sparse internal pores; Cu particles are agglomerated over a large area, and the catalytic active sites are wrapped by the carbon layer with extremely low exposure. 2) Cu3Ni1, Cu2Ni1, Cu1Ni1, Cu1Ni2 ( Figure 6 Chinese BD Figure 7 a): The main body of the material is a porous carbon sheet matrix with folded stacking, containing only a small number of short and fine carbon fragments; the sheet-like carbon substrate occupies the absolute majority, the carbon sheets are stacked disorderly, and the metal particles show local aggregation, making it difficult to construct unobstructed porous mass transfer channels. 3) Cu1Ni4, Cu1Ni8 ( Figure 7 Medium-grade Cd): Excessive nickel content will destroy the regular folded structure of carbon sheets, inhibit the formation of porous matrix, cause severe carbon sheet breakage, large-area collapse of the layered structure, a significant reduction in matrix porosity, and a significant exacerbation of metal particle agglomeration. 4) Sulfur-free Cu1Ni3 ( Figure 7 (b) The overall structure exhibits a regular, folded, stacked porous carbon sheet matrix. The carbon sheets are tightly stacked with abundant folds, but some areas are overly dense, resulting in a relatively low overall porosity. The Cu-Ni alloy metal particles are unevenly attached, with some particles stacking and covering the active sites on the carbon sheet surface. In summary, at a Cu / Ni molar ratio of 1:3, the Cu-Ni alloy can optimally catalyze the cracking and reconstruction of g-C3N4, forming a porous carbon sheet matrix with well-developed folds and a complete structure. The metal active sites are best dispersed, providing an excellent structural basis for the catalytic reaction.

[0096] 2. Effect of total metal content on morphology control SEM microstructure images of Cu1Ni3 / NC electrocatalysts with different total metal loadings are shown below. Figure 13 As shown, the electrocatalyst sample prepared with a total metal content of 25 mmol exhibited the best microstructure. The electrocatalyst prepared with a total metal content of 15 mmol ( Figure 13 (a) Using wrinkled stacked carbon sheets as the matrix, the carbon framework is well-formed, but the carbon sheets are densely stacked, the pores are poorly developed, and the number of pores is small. Furthermore, the low metal loading results in sparse Cu-Ni alloy particles on the carbon sheet surface, insufficient effective active sites, and difficulty in providing a sufficient electrocatalytic reaction interface and mass transfer channel. Electrocatalysts were prepared with a total metal content of 25 mmol. Figure 13(b) Possesses a regular and abundant pleated porous carbon sheet structure. The carbon sheets interweave to form interconnected hierarchical channels, ensuring smooth mass transfer. Cu-Ni alloy particles are uniformly anchored on the carbon sheet surface and in the pleats, exhibiting uniform particle size and no agglomeration. The active sites are fully exposed, providing excellent structural support for the electrocatalytic ammonia production reaction. Electrocatalyst prepared with 35 mmol total metal content ( Figure 13 (c) Due to excessive metal loading, the regular pleated porous structure of the carbon sheets is severely damaged, the framework is twisted and collapsed, and a large number of pores are blocked. At the same time, excessive metal particles agglomerate and accumulate severely, burying the matrix and metal active sites, significantly reducing site utilization, and hindering reactant diffusion and product desorption. In summary, when the total metal loading is 25 mmol, the Cu1Ni3 / NC electrocatalyst can form a porous carbon matrix with complete structure and well-developed pores, with better metal particle dispersion and more sufficient active sites, providing an excellent microstructural basis for the electrocatalytic reduction of ammonia production.

[0097] 3. Effect of sulfur doping amount on morphology control The microstructure of S-Cu1Ni3 / NC electrocatalysts with different sulfur doping amounts is as follows: Figure 26 As shown, for 0.05S-Cu1Ni3 and 0.1S-Cu1Ni3 (preferred sulfur-doped samples): sulfur atoms successfully embed into the carbon lattice of the porous carbon sheet matrix, effectively repairing carbon skeleton defects and optimizing the microstructure of the carbon sheet; the modified porous carbon sheet has richer folds, and the layers are loosely connected to form an open and well-developed multi-level pore structure; at the same time, sulfur doping can precisely control the electronic state of the carbon matrix surface, effectively refine Cu-Ni alloy nanoparticles, and significantly improve the monodispersity of metal particles. For 0.2S-Cu1Ni3 and 0.4S-Cu1Ni3 (high sulfur excess doping): under high temperature conditions, excess sulfur element easily generates sulfide particles, which agglomerate and accumulate on the surface of the carbon sheet, blocking the inherent pores of the matrix; at the same time, excessive sulfur doping will destroy the integrity of the carbon sheet structure, causing the porous carbon sheet matrix to fracture, clump and collapse, and the metal active sites to be covered and shielded by sulfides, ultimately leading to a significant decrease in the number of effective catalytic sites. As the reference sample for Example 1, the 0.1S-Cu1Ni3 catalyst is composed of a large number of wrinkled and curled porous carbon sheets stacked in an interlaced manner, forming a continuous and interconnected three-dimensional porous layered network structure. The carbon sheets have regular morphology, uniform wrinkles, and complete structure, without any breakage or collapse. The Cu-Ni alloy nanoparticles are small in size, uniformly distributed, and stably embedded and anchored on the surface of the porous carbon sheet matrix, without the problem of high-temperature sintering and agglomeration. The carbon sheets interlock to form a rich multi-level pore structure of mesopores and macropores, which significantly improves the specific surface area of ​​the material, allowing for electrolyte wetting and NO3- filtration. - The substrate diffusion and reaction intermediate transport provide ample and unobstructed channels, ensuring the efficient conduction of electrocatalytic reactions.

[0098] II. XRD pattern analysis of phase structure The XRD pattern of the sulfur-free Cu1Ni3 / NC electrocatalyst is shown below. Figure 5 As shown, the spectrum shows three sets of sharp characteristic diffraction peaks, corresponding to the (111), (200), and (220) crystal planes of the Cu-Ni alloy, respectively. These peaks match the standard PDF card, proving that the copper-nickel alloy crystal phase was successfully formed. The spectrum does not show individual Cu or Ni elemental diffraction peaks, indicating that Cu and Ni atoms are uniformly dissolved to form an alloy without phase separation. The baseline is flat with no obvious impurity peaks, indicating the absence of metal oxides and carbide impurities, and the material has high crystal purity.

[0099] The XRD patterns of Cu1Ni3 / NC electrocatalyst and 0.1S-Cu1Ni3 / NC electrocatalyst are shown below. Figure 24 As shown, the characteristic peaks of the two curves almost completely overlap, proving that moderate sulfur doping does not destroy the crystal structure of Cu-Ni alloy; sulfur is a trace lattice dopant, and no independent metal sulfide crystal phase is generated, with no additional sulfide diffraction peaks; sulfur doping only modulates the electronic structure of the carbon matrix and does not change the crystal phase composition of the metal active center.

[0100] III. Element Valence State XPS Fine Spectral Analysis like Figure 3-4 As shown in Figures 21-22, the Cu 2p spectrum can be separated into Cu... 0 / Cu + Cu 2+ Characteristic peaks; Ni 2p spectrum contains Ni 0 / Ni 2+ Characteristic peaks. Zero-valence state Cu metal. 0 Ni 0 The main active sites for catalysis are small amounts of divalent metals derived from slight surface oxidation. Compared with sulfur-free Cu1Ni3 / NC, the binding energies of Cu and Ni characteristic peaks in the 0.1S-Cu1Ni3 / NC sample show a slight shift, indicating a strong electronic interaction between the sulfur-doped carbon support and the Cu-Ni alloy, which can regulate the adsorption energy of the metal sites for nitrate nitrogen and hydrogenation intermediates.

[0101] like Figure 23 As shown, S 2p can be decomposed into S 2p 3 / 2 S 2p 1 / 2 The two sets of characteristic peaks correspond to CSC-doped sulfur in the carbon lattice, and there are no characteristic peaks of metal sulfides or elemental sulfur. This directly confirms that sulfur has been successfully doped into the folded and stacked porous carbon sheet matrix, existing in the form of covalent doping, and constructing an electronically controlled "sulfur bridge" structure.

[0102] IV. Surface hydrophilicity / hydrophobicity and roughness analysis like Figure 1 , Figure 2 , Figure 12 As shown, the water contact angles of electrocatalysts with different Cu / Ni ratios were all >100°, exhibiting overall hydrophobic characteristics. The high-nickel samples Cu1Ni0 / NC and Cu1Ni8 / NC showed excessively high contact angles, indicating strong hydrophobicity and hindering electrolyte penetration into the porous carbon matrix, thus impeding substrate mass transfer. The optimal contact angle for Cu1Ni3 / NC was 102.9°, with moderate hydrophobicity, effectively suppressing ineffective water molecule adsorption and reducing hydrogen evolution competition while ensuring sufficient electrolyte wetting of the porous carbon sheet matrix with its folded structure. In the water contact angle tests of Cu1Ni3 / NC electrocatalysts prepared with different total metal loadings, the Cu1Ni3 / NC electrocatalyst prepared with a total metal loading of 25 mmol showed the best contact angle. In summary, the Cu1Ni3 / NC electrocatalyst prepared with a total metal loading of 25 mmol exhibited the best water contact angle at 102.9°. Figure 25 As shown, after doping with sulfur, the contact angle of 0.1S-Cu1Ni3 / NC is further reduced to 77.3°, making it easier for the electrolyte to penetrate into the porous interior of the carbon matrix and enhancing the substrate mass transfer rate.

[0103] like Figure 39 As shown, the surface roughness of the catalyst fluctuates significantly with changes in the Cu / Ni ratio and sulfur doping amount; the roughness of 0.1S-Cu1Ni3 / NC is in a moderate range. Moderate sulfur doping optimizes the micro-undulations of the carbon matrix surface and balances wettability; when sulfur is excessive, the surface sulfide protrusions lead to a sharp increase in roughness, which disrupts the mass transfer interface. Figure 40 These are confocal laser scanning microscopy images of the Cu2Ni1 / NC, Cu1Ni3 / NC, and 0.1S-Cu1Ni3 / NC electrocatalysts. The Cu2Ni1 / NC surface exhibits the largest surface undulations, with numerous deep pits; the Cu1Ni3 / NC surface shows reduced undulations; and the sulfur-doped 0.1S-Cu1Ni3 / NC forms a continuous trench-pore structure. The results indicate that controlling the Cu / Ni molar ratio and sulfur doping can alter the three-dimensional surface roughness of the catalysts. Sulfur doping can construct interconnected hierarchical trenches, increasing the effective reaction area of ​​the electrode, promoting reactant mass transfer, and facilitating the electrocatalytic reduction of nitrate nitrogen to ammonia.

[0104] V. Electrochemical Performance Analysis LSV curves of electrocatalysts with different Cu / Ni ratios are shown below. Figure 8 As shown, the dashed line represents the area without NO3. - Blank electrolyte; solid line represents electrolyte containing nitrate nitrogen; all catalysts are present in the presence of NO3. -The reduction current in the system was much higher than that in the blank group, proving that the material has electrocatalytic nitrate reduction activity. Under the same negative potential, the Cu1Ni3 / NC reduction current density was the highest in the whole group, and the electrocatalytic reduction kinetics were optimal. The current density of the pure copper and unbalanced nickel ratio samples was significantly lower, which is attributed to the incomplete porous carbon sheet matrix network with wrinkled stacking, the agglomeration of metal particles, and the high resistance to electron transport.

[0105] LSV curves of Cu1Ni3 / NC electrocatalysts with different total metal loadings are shown below. Figure 14 As shown, when the total metal loading is 15 mmol (M15), there are insufficient metal active sites, resulting in a low catalytic current; when the total metal loading is 35 mmol (M35), metal particles agglomerate, exacerbating the hydrogen evolution side reaction. When the total metal loading is 25 mmol (M25), the catalytic current is low in the presence of NO3. - The system exhibits a high reduction current density, indicating strong catalytic activity for the reduction of nitrate nitrogen to ammonia and effective suppression of hydrogen evolution competition reactions. Therefore, it has excellent electrochemical performance when the total metal loading is 25 M.

[0106] like Figure 27 As shown, with a fixed Cu:Ni ratio of 1:3, the 0.1S-Cu1Ni3 polarization curve exhibits the highest peak reduction current density. The sulfur-free sample shows a lower reduction current and a higher proportion of hydrogen evolution byproduct current. The 0.4S high-sulfur-doped sample shows a significant current decay, with sulfides covering the active sites and hindering electron transfer and substrate adsorption. Lattice sulfur doping can optimize the band structure of the carbon support, accelerate electron transfer from the folded, stacked porous carbon sheet matrix to the Cu-Ni active centers, and enhance NO3- absorption. - Reduction kinetic rate.

[0107] VI. Catalytic Performance Analysis like Figure 9 As shown, in different copper-nickel ligand variable groups (-0.8V), Cu1Ni3 / NC exhibits an ammonia selectivity of 84% and a nitrate nitrogen conversion rate of 84%, far superior to single copper catalysts (selectivity only 67%, conversion rate 79%). The hydrogenation capacity of single copper metal intermediates is insufficient, such as... Figure 10 As shown, the cumulative peak value of nitrite nitrogen in the single copper catalyst reached 22 mg / L. Bimetallic synergy significantly improved the directed ammonia production capacity. The cumulative peak value of nitrite nitrogen in Cu1Ni3 / NC was 7.50 mg / L. Cu was responsible for adsorbing nitrite nitrogen and breaking NO bonds, while Ni accelerated the hydrogenation conversion of toxic nitrite nitrogen and effectively suppressed intermediate accumulation. Figure 11 As shown, Cu1Ni3 / NC and Cu1Ni4 / NC exhibit high ammonia yields, with Cu1Ni3 / NC achieving an ammonia yield of 290.83 μg·h⁻¹. -1 ·cm -2 It is superior to a single copper catalyst (ammonia yield of 234.43 μg·h⁻¹).-1 ·cm -2 ).

[0108] like Figure 15-17 As shown, when the total metal content is 35 mmol (-0.8V), although the peak value of nitrite nitrogen accumulation decreases, the conversion rate and ammonia yield of the copper-nickel catalyst (Cu1Ni3 / NC) decrease significantly, and the ammonia conversion performance is poor. When the total metal content is 25 mmol, the conversion rate and ammonia yield are the highest, and the ammonia conversion performance is good, but the accumulation of nitrite nitrogen intermediates is high and the catalyst active sites are insufficient, which needs to be further improved.

[0109] like Figure 18-20 As shown, during the investigation of the copper-nickel catalyst (Cu1Ni3 / NC) from a low cathode overpotential of -0.5V to a high cathode overpotential of -0.8V, in the initial stage, the Faraday efficiency, selectivity, conversion, and ammonia yield increased with increasing overpotential, but this increase was not continuous. When the overpotential exceeded a certain range, such as -0.8V, the Faraday efficiency, selectivity, conversion, and ammonia yield began to decrease significantly. Figure 18 , Figure 20 When using electrochemical catalytic transammoniation, a higher overpotential is not necessarily better. The reduction in the accumulation of nitrite intermediates exhibits a certain overpotential dependence, gradually decreasing as the cathode overpotential increases. Figure 19 Therefore, achieving better electrocatalytic performance in the reduction of nitrate nitrogen to ammonia inevitably leads to increased accumulation of nitrite nitrogen intermediates. Copper-nickel catalysts (Cu1Ni3 / NC) are insufficient to simultaneously improve both the electrocatalytic performance of nitrate nitrogen reduction to ammonia and the accumulation of nitrite nitrogen intermediates, and further improvements are needed. Figures 28-30 As shown, at a potential of -0.7V, for different sulfur doping variable groups, except that the conversion rate decreases significantly with increasing sulfur doping amount compared to the copper-nickel catalyst (Cu1Ni3 / NC), the Faraday efficiency and selectivity remain similar to those of the copper-nickel catalyst (Cu1Ni3 / NC). Figure 28 The peak nitrite nitrogen concentrations of different sulfur doping variables were significantly lower than those of Cu1Ni3 / NC (12.53 mg / L), especially the peak nitrite nitrogen concentration of 0.1S-Cu1Ni3 / NC (6.5 mg / L), which showed the largest decrease. This is attributed to the electronic regulation of the "sulfur bridge" constructed by the lattice sulfur, which optimizes the adsorption energy of the intermediate, directionally transports active hydrogen to bind with nitrite nitrogen, accelerates the binding of the two, and significantly suppresses the hydrogen evolution side reaction. Figure 29 In different sulfur doping variable groups, the ammonia yield of 0.1S-Cu1Ni3 / NC was 342.08 μg·h⁻¹. -1 ·cm -2 The yield of low-sulfur ammonia using 0.05S-Cu1Ni3 / NC was 343.08 μg·h⁻¹. -1 ·cm-2 The improvement was limited; the yield of the 0.2S-Cu1Ni3 / NC excess sulfur sample dropped to 283.53 μg·h⁻¹. -1 ·cm -2 The ammonia yields of 0.1S and 0.05S sulfur-doped catalysts were similar to those of the copper-nickel catalyst (Cu1Ni3 / NC) (354.63 μg·h⁻¹). -1 ·cm -2 () Figure 30 In summary, different sulfur doping variable groups significantly reduced the peak value of nitrite accumulation while maintaining similar ammonia selectivity, Faraday efficiency, conversion rate, and ammonia yield as the copper-nickel catalyst (Cu1Ni3 / NC). The 0.1S-Cu1Ni3 / NC group showed the best performance, indicating that sulfur doping further optimizes the hydrogenation reaction pathway and accelerates the consumption of intermediate products, demonstrating the superiority of sulfur doping.

[0110] like Figures 31-38The multi-potential performance comparison shown indicates that in the operating potential range of -0.5 to -0.7 V (vs. RHE), the 0.1S-Cu1Ni3 / NC catalyst, through the directional transport of active hydrogen and nitrite nitrogen via a sulfur element bridge, inhibits the hydrogen evolution reaction. While significantly suppressing the accumulation of nitrite nitrogen intermediates, it also exhibits excellent Faradaic efficiency, selectivity, conversion rate, and ammonia yield, demonstrating superior electrocatalytic performance for nitrate nitrogen to ammonia conversion. At an operating potential of -0.8 V, the increase in active hydrogen intensifies the competition for the hydrogen evolution reaction, leading to an initial accumulation of nitrite nitrogen exceeding that of Cu1 under the action of the 0.1S-Cu1Ni3 / NC catalyst. The Ni3 / NC catalyst, however, exhibits improved performance due to the active hydrogen regulation effect of the sulfur bridge in the 0.1S-Cu1Ni3 / NC catalyst. This ensures the continuous and efficient combination of active hydrogen with nitrite nitrogen under the action of the 0.1S-Cu1Ni3 / NC catalyst, significantly suppressing the hydrogen evolution reaction. The accumulation of nitrite nitrogen subsequently decreases significantly compared to the Cu1Ni3 / NC catalyst. Furthermore, the conversion rate, ammonia selectivity, and ammonia yield of 0.1S-Cu1Ni3 / NC are consistently superior to those of sulfur-free Cu1Ni3 / NC, demonstrating the potential-wide applicability of sulfur doping's performance enhancement effect. Sulfur doping successfully suppresses nitrite nitrogen accumulation, improves selectivity, inhibits hydrogen side reactions at low potentials, and regulates the hydrogen reaction pathway at high potentials. In summary, XRD / XPS analysis of the Cu:Ni=1:3 metal ratio showed no metal particle broadening / agglomeration signals, indicating that there was no significant agglomeration of Cu and Ni. At high temperatures, Cu-Ni catalyzed carbon nitride cracking led to the directional growth of a N-doped, wrinkled, stacked porous carbon substrate. The precursor contained a sulfur source and was simultaneously doped with carbon, forming a "sulfur-doped porous carbon substrate supporting Cu-Ni alloy" structure. Furthermore, the porous carbon substrate served as a conductive carrier, possessing a large specific surface area and excellent conductivity, allowing for the uniform dispersion of copper-nickel bimetallic active sites and effectively preventing particle agglomeration and deactivation. The continuous conductive network of the porous carbon substrate, the sulfur-regulated electronic structure, and the bimetallic synergistic denitrification and ammonia production performance perfectly matched the characteristics of this composite structure, exhibiting high catalytic current density and excellent stability. Thus, the 0.1S-Cu1Ni3 / NC electrocatalyst (Example 1), prepared with a Cu:Ni=1:3 metal ratio and moderate doping of 0.1 g thiourea, achieves optimal structure-performance matching. 1. Microstructure: Complete and continuous three-dimensional network of porous carbon sheet matrix, with uniformly dispersed Cu-Ni alloy particles and well-developed pores; 2. Phase and valence state: XRD confirmed the pure Cu-Ni alloy crystal phase, and XPS proved that sulfur covalently doped carbon framework and that there is an electronic modulation effect between sulfur and metal; 3. Surface characteristics: Moderate hydrophobicity and reasonable roughness, balancing the inhibition of hydrogen evolution and electrolyte mass transfer; 4. Electrochemistry: LSV exhibits optimal reduction kinetics and low electron transport resistance; 5. Catalytic performance: It has the highest nitrate nitrogen conversion rate, ammonia selectivity, and ammonia yield, and the lowest accumulation of toxic intermediates of nitrite nitrogen.

[0111] Imbalanced copper-nickel ratios, absence of sulfur doping, and excessive sulfur doping can all damage the porous carbon substrate structure, alter the electronic states of metals, and block active sites, ultimately leading to a decline in electrochemical kinetics and a comprehensive deterioration of the overall catalytic performance for denitrification and ammonia production.

[0112] The electrocatalyst prepared in this invention can be coupled to a photovoltaic system to achieve low-energy, green operation, such as... Figure 41 As shown, using the electrocatalyst and working electrode prepared in Example 1, along with a platinum sheet counter electrode and a saturated potassium chloride and silver chloride reference electrode, a three-electrode electrolysis device was constructed. Powered by solar energy, it can treat actual wastewater containing 500 mg / L nitrate, and the effluent can be used as raw material for the production of liquid nitrogen fertilizer for agriculture. It is suitable for treating agricultural, municipal, and industrial wastewater, simultaneously purifying nitrate-containing wastewater and recovering green ammonia resources.

[0113] Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions provided above are only for illustrating the principles of the present invention and are not intended to limit the scope of protection of the present invention. Various modifications, substitutions, or improvements can be made to the present invention without departing from the spirit and substance of the invention, and all such modifications, substitutions, or improvements should fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing an electrocatalyst for removing nitrate nitrogen from an aquatic environment and directionally producing ammonia, characterized in that the step... include: The sulfur-doped graphitic carbon nitride precursor and the copper-nickel bimetallic complex precursor were ground and mixed, then ball-milled to homogenize them, and then calcined in an inert atmosphere to obtain the product. The mass ratio of the sulfur-doped graphitic carbon nitride precursor to the copper-nickel bimetallic complex precursor is 1.5-2.5:

1. The preparation of the sulfur-doped graphitic carbon nitride precursor includes: grinding and mixing melamine, maleic hydrazine, and thiourea, followed by calcination under an inert atmosphere; the mass ratio of melamine, maleic hydrazine, and thiourea is 10-45:0.1-1.5:

1. The preparation of the copper-nickel bimetallic complex precursor includes: mixing and reacting copper salt, nickel salt, and melamine in an alcohol-water solution; in the alcohol-water solution, the total concentration of metal ions is 0.05-0.2 mol / L, the molar ratio of copper ions in the copper salt to nickel ions in the nickel salt is 1:0.3-8, and the concentration of melamine is 0.01-0.1 g / mL.

2. The preparation method according to claim 1, characterized in that, The ball milling homogenization process includes the following repeated steps: forward rotation, dwell, reverse rotation, dwell, with a ball mill speed of 300-500 r / min, forward rotation time of 10-20 min, reverse rotation time of 10-20 min, and dwell time of 10-20 min.

3. The preparation method according to claim 1, characterized in that, The sulfur-doped graphitic carbon nitride precursor and the copper-nickel bimetallic complex precursor are mixed and homogenized by ball milling, and then calcined in an inert atmosphere at a temperature of 800-900℃ for 4-5 hours.

4. The preparation method according to claim 1, characterized in that, After the melamine, maleic hydrazide, and thiourea are ground and mixed, they are calcined in an inert atmosphere at a temperature of 500-600℃ for 4-5 hours.

5. An electrocatalyst for removing nitrate nitrogen and directionally producing ammonia, characterized in that, Prepared by the method according to any one of claims 1-4, Cu-Ni alloy catalyzes the cracking of graphitic carbon nitride to generate a folded and stacked porous carbon sheet matrix, sulfur atoms are embedded in the carbon lattice of the porous carbon sheet matrix, and Cu-Ni alloy nanoparticles are uniformly embedded and anchored on the surface of the porous carbon sheet matrix; the porous carbon sheet matrix is ​​stacked and overlapped to construct a continuous and interconnected three-dimensional porous sheet network, and mesopores and macropores are distributed between the porous carbon sheet matrix.

6. The application of the electrocatalyst described in claim 5 in preparing a working electrode or electrolysis device for removing nitrate nitrogen and producing ammonia in a targeted manner, or in preparing liquid nitrogen fertilizer.

7. A working electrode for removing nitrate nitrogen and directionally producing ammonia, characterized in that, The electrocatalyst of claim 5, comprising a matrix and a coating matrix.

8. An electrolytic device for removing nitrate nitrogen and directionally producing ammonia, characterized in that, It contains the working electrode as described in claim 7.

9. A method for removing nitrate nitrogen and directionally producing ammonia, characterized in that, The steps include: At room temperature and pressure, the sample solution is treated using the electrolysis device described in claim 8 to reduce nitrate nitrogen in the sample solution to ammonium ions.

10. A liquid nitrogen fertilizer, characterized in that, It is prepared by the method described in claim 9.